Primary scrotal lipoma posing a diagnostic quandary: Experience from northern Tanzania, a case report - Orgeness Jasper Mbwambo; Angela Pallangyo; Jasper Saidi Mbwambo; Frank Bright; Alfred K. Mteta; Jacques Bogdanowicz; Bartholomeo Nicholaus Ngowi (Clinical Case Reports, 2023)
Abstract Primary scrotal lipoma is a rare urological diagnosis. It is usually diagnosed incidentally as most of time initial diagnosis may be confused with other common etiology of scrotal masses. A rare case of scrotal lipoma with initial misdiagnosis of hydrocele at primary health facility is presented in this article.